FILOSOFI HIDUP MASYARAKAT KRUCIL : ANALISIS KETAHANAN EKONOMI PETERNAK SAPI PERAH TERHADAP DAMPAK VIRUS PMK (PENYAKIT MULUT DAN KUKU) BERDASARKAN KONSEP EKONOMI ISLAM - Sabrina, Anadia; Huda, Nurul (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2023)
Foot and Mouth Disease (FMD) Food and Mount Disease is caused by a virus that attacks cloven-hoofed animals, one of which is cattle. This virus can cause livestock health to be disrupted, so that the sale value and productivity in producing milk decreases. This of course has a significant impact on the economy, especially for residents who rely on income from the sale of cow's milk. The purpose of this study was to identify the level of economic resilience of the Krucil village community as a benchmark for people experiencing the same problems. The research was conducted using a qualitative method by taking a case study approach to several informants from related agencies and local residents who are members of farmer groups. The results of the study show that the Krucil community was able to survive in a situation affected by PMK, this happened because of the potential, tenacity, cooperation and optimism of the residents. So as to create economic resilience based on love for the creator, as well as nature that needs to be preserved and looked after.